La quinoa chilota (Ediciones UC, 2019)
The Big Island of Chiloé represents an extraordinary reserve of biodiversity. Its territory forms a natural capital of great wealth, since it is home to a wide variety of plant species. The inhabitants of the island, part of them of Huilliche origin, have cultivated these species over time -including quinoa- for their agri-food use using ancestral techniques transmitted from generation to generation, with women being the main guardians of these practices. and those responsible for its preservation. Within the diversity of species on the island, Chiloé quinoa stands out as a unique genetic resource with great food potential, of high biological, ecological, nutritional, social and cultural value; however, it is a variety that is little known at the national level and its cultivation is carried out by a small number of farmers, mostly women. The book 'La quinoa chilota' brings together the results of a study, supported by the Foundation for Agrarian Innovation (FIA), on this type of quinoa. The eight chapters that compose it were developed by a multidisciplinary team of researchers from the QuinoaLab group of the Pontificia Universidad Católica de Chile in order to develop a baseline to support the agroecological production of Chiloé quinoa that contributes to the conservation of an important genetic resource for the local and global agricultural heritage. This publication seeks to spread scientific knowledge and show the relevance of Chiloé quinoa to a wide public, both scientific and general.